2023
DOI: 10.1088/1674-4926/44/5/052801
|View full text |Cite
|
Sign up to set email alerts
|

A novel SiC high-k superjunction power MOSFET integrated Schottky barrier diode with improved forward and reverse performance

Abstract: A new SiC superjunction power MOSFET device using high-k insulator and p-type pillar with an integrated Schottky barrier diode (Hk-SJ-SBD MOSFET) is proposed, and has been compared with the SiC high-k MOSFET (Hk MOSFET), SiC superjuction MOSFET (SJ MOSFET) and the conventional SiC MOSFET in this article. In the proposed SiC Hk-SJ-SBD MOSFET, under the combined action of the p-type region and the Hk dielectric layer in the drift region, the concentration of the N-drift region and the current spreading layer ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 45 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…From this figure, it can be observed that both the BV and R on,sp are decreased when the interface charge density varies from −10×10 11 cm −2 to 10×10 11 cm −2 , this is because the interface charge alters the effective doping concentration of the device. A negative interface charge density implies a decrease in effective doping concentration, while a positive interface charge density implies an increase in effective doping concentration [23]. For TMOS, higher doping concentration in the drift region leads to lower BV and R on,sp .…”
Section: Device Structure and Mechanismmentioning
confidence: 99%
“…From this figure, it can be observed that both the BV and R on,sp are decreased when the interface charge density varies from −10×10 11 cm −2 to 10×10 11 cm −2 , this is because the interface charge alters the effective doping concentration of the device. A negative interface charge density implies a decrease in effective doping concentration, while a positive interface charge density implies an increase in effective doping concentration [23]. For TMOS, higher doping concentration in the drift region leads to lower BV and R on,sp .…”
Section: Device Structure and Mechanismmentioning
confidence: 99%
“…Meanwhile, novel structures have been published to further improve device performance. A device formed with a high-k material offers a wider charge balance window than a novel SJ MOSFET [ 14 , 15 ] and, hence, reduces manufacturing error. Recently, deep-trench SJ MOSFETs with better short-circuit performance and electric field distribution have also been obtained [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…And the commercial SiC MOSFET (metal-oxide-semiconductor field-effect transistor), JFET (junction field-effect transistor), and SBD (Schottky barrier diode) products are already widely used and are extremely significant components of the power electronics systems [4][5][6][7]. And the advancement of SiC wafers and process technologies provide more possibilities for the design and realization of SiC power devices, and the SiC trench MOSFETs have also been commercialized and have been extensively researched [8][9][10][11][12]. However, the issues of the oxidation process of SiC introduce high interface states density at the SiO 2 /SiC interface and low electron mobility of the channel inversion layer in the SiC trench MOSFETs still exists.…”
Section: Introductionmentioning
confidence: 99%